The interdependence of currencies among South East Asia / Muhammad Firdaus Sharil - Sharil, Muhammad Firdaus (Faculty of Business and Management, 2020)
The aim of this study is to investigate the interdependence of currency among South East Asia countries. The study used is Multiple Linear Regression in order to find the relationship among those countries. The monthly exchange rate is collected from October 2009 until September 2019. From the results it reveals that all this currencies in this study have a significant relationship with South East Asia countries. It means that there are interdependencies among these South East Asia countries’ currencies and this result further my understanding of the relationship between exchange rate in South East Asia. Furthermore, it should be useful for regulators, investors and speculators for making a wise investment in future.